ANALISIS MODEL PEMBELAJARAN ALTERNATIF DI MASA PANDEMI COVID-19 - Hastuti Titi Mildawati (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Teachers as the vanguard in the teaching and learning process must present an attractive and effective learning model in order to achieve a quality education that must be in the Covid-19 pandemic. However, the sudden policy resulted in teachers experiencing inequality. Due to the unpreparedness of education stakeholders in dealing with curriculum changes. Therefore, this article examines the learning model used by teachers after the enactment of government policies during the Covid-19 pandemic, then maps the obstacles faced in learning during the pandemic and analyzes the appropriate learning model as a solution to obstacles in the field. The method used in this research is descriptive qualitative by collecting data from the results of educators' survey data through google form. From the results of the study, it was found that there were three learning models used by teachers in the Covid-19 pandemic, namely daring/the online learning model (dalamjaringan), luring/offline (luarjaringan), and guling (guru keliling). This tri model is used based on learning in the field by looking at the conditions of the facilities and infrastructure for teachers and students